Porous catalyst, preparation method and application thereof, and method for preparing 1, 2-propylene glycol

By developing Ce-Ni porous catalysts with microporous structures, the problems of poor catalyst recycling and complex reactions in the prior art are solved, and an efficient and simple preparation process of 1,2-propylene glycol is achieved.

CN119838603APending Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311348717.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, when using polyhydroxy biomass to prepare 1,2-propanediol, the catalyst has poor recycling ability, additional additives are required, and the reaction process is complicated.

Method used

A porous catalyst, including oxides of Ce and Ni distributed on oxides of Ce, is developed to form a catalyst with a microporous structure by a specific preparation method for catalyzing the conversion of polyhydroxy compounds to 1,2-propanediol in hydrolysis and hydrogenation reactions.

Benefits of technology

The catalyst exhibits high conversion and selectivity when preparing 1,2-propanediol. The reaction is a one-step reaction without additional additives. The catalyst is stable, has good circulation and is easy to recover.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838603A_ABST
    Figure CN119838603A_ABST
Patent Text Reader

Abstract

The invention relates to the field of catalytic chemistry, and discloses a porous catalyst, a preparation method and application thereof, and a method for preparing 1, 2-propylene glycol. In an XRD (X-Ray Diffraction) pattern of the catalyst, a diffraction peak exists at a position of 44.5 + / -0.5 and / or 51.8 + / -0.5; the catalyst has a microporous structure. The catalyst has excellent catalytic activity, and especially when the catalyst is used in hydrolysis and hydrogenation reactions, the catalyst has excellent catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalytic chemistry, and in particular to a porous catalyst and a preparation method and application thereof, and a method for preparing 1,2-propylene glycol. Background Art

[0002] Polyhydroxy biomass is abundant and easily available. The production of chemicals by polyhydroxy biomass catalysis has the following advantages: 1. Good atom economy; 2. Easy to obtain raw materials; 3. Renewable resources; 4. Low carbon dioxide emissions. 1,2-propylene glycol is widely used in unsaturated resins, food and cosmetics. At present, the technology for the production of 1,2-propylene glycol by polyhydroxy biomass catalysis is not yet mature. Therefore, the development of new catalysts and new processes can promote the industrialization of this technology, thereby generating huge environmental and economic benefits.

[0003] CN104549347A directly uses glycerol as a raw material to hydrogenate 1,2-propylene glycol. This method requires the use of a variety of metal oxides to prepare catalysts and requires the use of additional additives; CN102731257A and CN103833513A mainly use tungsten-based catalysts, alkali metal oxides and hydrogenation catalysts to catalytically convert polyhydroxy compounds. Using cellulose as a substrate, more than 30% of 1,2-propylene glycol conversion can be achieved. Its use requires the use of a composite catalyst, and the catalyst has poor recyclability; CN104961628 uses glucose as a raw material to obtain more than 20% of 1,2-propylene glycol. This method requires two intermittent reaction processes in a high-pressure reactor; CN106866374A uses xylose or oligoxylose as a raw material, transition metals as catalytic active centers, and alkaline compounds as additives to achieve the production of 1,2-propylene glycol and ethylene glycol, wherein the yield of propylene glycol is 20-40%, but it requires the addition of additives. Summary of the invention

[0004] The purpose of the present invention is to provide a new porous catalyst having excellent catalytic activity, especially when the catalyst is used in hydrolysis and hydrogenation reactions, it has excellent catalytic performance. For example, when the catalyst is used in the one-pot preparation of 1,2-propylene glycol, it can better catalyze the conversion of polyhydroxy compounds into 1,2-propylene glycol. The reaction process is a one-step reaction and does not require the addition of additional additives, and the reaction process is simple.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a porous catalyst, which includes Ce oxide and Ni distributed on Ce oxide; wherein, in the XRD spectrum of the catalyst, there are diffraction peaks at 44.5±0.5 and / or 51.8±0.5; and the catalyst has a microporous structure.

[0006] The second aspect of the present invention provides a method for preparing the porous catalyst of the present invention, which comprises: (1) contacting a Ce source, a Ni source, a template, a foaming agent and a solvent to form a gel, optionally drying, and then performing a first calcination to obtain an aerogel; (2) performing a second calcination on the aerogel in a reducing atmosphere.

[0007] The third aspect of the present invention provides the use of the catalyst of the present invention in hydrolysis and hydrogenation reactions.

[0008] A fourth aspect of the present invention provides a method for preparing 1,2-propylene glycol, the method comprising: hydrolyzing and hydrogenating a polyhydroxy compound in the presence of water, hydrogen and the catalyst of the present invention.

[0009] Through the above technical scheme, the catalyst provided by the present invention includes Ce oxide and Ni distributed on Ce oxide; wherein, in the XRD spectrum of the catalyst, there are diffraction peaks at 44.5±0.5 and / or 51.8±0.5; the catalyst has a microporous structure, and the metal active components are not easy to lose during use. When it is used for preparing 1,2-propylene glycol from polyhydroxy compounds, the substrate conversion rate and the product 1,2-propylene glycol selectivity are both very high, and the reaction process is a one-step reaction, and no additional additives are required. The reaction process is simple, the catalyst is stable, the recyclability is good, and it is easy to recover. No catalyst deactivation is observed after four cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 is a SEM electron microscope image of the catalyst obtained in Example 1;

[0011] Figure 2 is an X-ray photoelectron spectroscopy (XPS) diagram of the Ce element contained in the catalyst obtained in Example 1;

[0012] Figure 3 is an X-ray photoelectron spectroscopy (XPS) diagram of the Ni element contained in the catalyst obtained in Example 1;

[0013] Figure 4 is the XRD spectrum of the catalyst obtained in Example 1. DETAILED DESCRIPTION

[0014] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0015] The first aspect of the present invention provides a porous catalyst, which includes Ce oxide and Ni distributed on the Ce oxide; wherein, in the XRD spectrum of the catalyst, there are diffraction peaks at 44.5±0.5 and / or 51.8±0.5; and the catalyst has a microporous structure.

[0016] In the present invention, it should be noted that the oxide of Ce can be CeO2, or can be an oxide of Ce in other forms, mainly CeO2, and Ni distributed on the oxide of Ce is in a valence state of 0. The catalyst of the present invention has good catalytic activity and stability, so that when preparing 1,2-propylene glycol, a better conversion rate and a comprehensive effect of selectivity of 1,2-propylene glycol can be obtained, and the cyclic stability of the catalyst allows the catalyst to maintain good activity after repeated use.

[0017] In the present invention, the valence state of the metal in the catalyst is characterized by X-ray photoelectron spectroscopy.

[0018] According to the present invention, in some embodiments, the XRD spectrum of the catalyst has at least one diffraction peak at 2θ of 28.5±0.5, 33±0.5, 44.5±0.5, 47.4±0.5, 51.8±0.5, 56.3±0.5, 59±0.5 and 69.3±0.5. By controlling the catalyst crystal form to have the characteristics of the aforementioned embodiment, the catalyst has the advantages of high selectivity and stability when used to prepare 1,2-propylene glycol.

[0019] According to the present invention, in some preferred embodiments, in the XRD spectrum of the catalyst, there are no diffraction peaks at 20±0.5, 40±0.5 and 50±0.5. By controlling the catalyst crystal form to have the characteristics of the aforementioned embodiment, the catalyst has the advantages of high selectivity and stability when used to prepare 1,2-propylene glycol.

[0020] According to the present invention, in some embodiments, the catalyst has a macroporous structure and a mesoporous structure. The catalyst having the above characteristics has excellent catalytic activity, and when used to prepare 1,2-propylene glycol, the catalyst has the advantages of high selectivity and stability.

[0021] According to the present invention, in some preferred embodiments, the macropore diameter of the catalyst is in the range of 60-30000 nm. The catalyst having the above characteristics has excellent catalytic activity, and when used to prepare 1,2-propylene glycol, the catalyst has the advantages of high selectivity and stability.

[0022] According to the present invention, in some preferred embodiments, the mesopore diameter of the catalyst is in the range of 2-50 nm. The catalyst having the above characteristics has excellent catalytic activity, and when used to prepare 1,2-propylene glycol, the catalyst has the advantages of high selectivity and stability.

[0023] In the present invention, the pore structure of the catalyst can be obtained through SEM images.

[0024] According to the present invention, in some preferred embodiments, the specific surface area of ​​the catalyst is in the range of 50-150 m 2 The catalyst having the above characteristics has excellent catalytic activity. When the catalyst is used to prepare 1,2-propylene glycol, it has the advantages of high selectivity and stability.

[0025] In the present invention, the specific surface area of ​​the catalyst is obtained by testing with a nitrogen adsorption instrument.

[0026] The pore size of the micropores in the present invention is less than 2 nm.

[0027] In the present invention, it should be noted that, generally, a certain amount of catalyst is prepared, and the macropore / mesopore pore size and / or specific surface area of ​​the prepared catalyst may be a fixed value or a range value, generally a range value, that is, the range value composed of the maximum size and the minimum size of the macropore pore size and the mesopore pore size of the catalyst in a field of view of the SEM image, and the specific surface area of ​​the catalyst is the range value composed of the maximum specific surface area and the minimum specific surface area in the prepared catalyst.

[0028] According to the present invention, in some preferred embodiments, in the catalyst, the mass ratio of Ni element to Ce element is not less than 0.064. The catalyst having the above characteristics has excellent catalytic activity, and the above catalyst has the advantages of high selectivity and stability when used to prepare 1,2-propylene glycol.

[0029] According to the present invention, in some more preferred embodiments, the mass ratio of Ni element to Ce element is 0.064-0.53:1, for example, 0.064:1, 0.136:1, 0.2:1, 0.3:1, 0.4:1, 0.53:1, or a range of any two of the above ratios. The catalyst having the above characteristics has better catalytic activity, and the above catalyst has the advantages of high selectivity and stability when used to prepare 1,2-propylene glycol.

[0030] In the present invention, the contents of Ni and Ce in the catalyst are measured by an inductively coupled plasma spectrometer.

[0031] The second aspect of the present invention provides a method for preparing the porous catalyst of the present invention, the preparation method comprising:

[0032] (1) contacting a Ce source, a Ni source, a template, a foaming agent and a solvent to form a gel, optionally drying, and then performing a first calcination to obtain an aerogel;

[0033] (2) The aerogel is subjected to a second calcination in a reducing atmosphere.

[0034] In the present invention, the template agent and the foaming agent act synergistically with each other, and the porous catalyst prepared with Ce source and Ni source as raw materials has the advantages of simple process, stable catalyst, good recyclability and easy recovery when used for preparing 1,2-propylene glycol from polyhydroxy compounds.

[0035] According to the present invention, in some embodiments, the template comprises an organic acid and an alcohol compound. By adopting the above-mentioned embodiment, a porous catalyst with a specific structural distribution can be formed, and when the prepared catalyst is used to prepare 1,2-propylene glycol from polyhydroxy compounds, it has better raw material conversion rate and 1,2-propylene glycol selectivity.

[0036] According to the present invention, in some embodiments, the organic acid is selected from polyacids. By adopting the above-mentioned embodiment, a porous catalyst with a specific structure distribution can be formed, and when the prepared catalyst is used to prepare 1,2-propylene glycol from polyhydroxy compounds, it has better raw material conversion rate and 1,2-propylene glycol selectivity.

[0037] In the present invention, the polyacid refers to an organic acid containing at least two carboxyl groups. In some preferred embodiments, the organic acid is selected from at least one of a dibasic acid (e.g., oxalic acid, malonic acid, succinic acid), a tribasic acid (e.g., citric acid) and a tetrabasic acid. By adopting the above-mentioned embodiment, a porous catalyst with a specific structural distribution can be formed, and the prepared catalyst has better selectivity for 1,2-propylene glycol when used in the preparation of 1,2-propylene glycol from polyhydroxy compounds.

[0038] According to the present invention, in some more preferred embodiments, the organic acid is a tribasic acid. By adopting the above-mentioned embodiment, a porous catalyst with a specific structural distribution can be formed, and the prepared catalyst has better 1,2-propylene glycol selectivity when used in preparing 1,2-propylene glycol from polyhydroxy compounds.

[0039] According to the present invention, in some preferred embodiments, the alcohol compound is selected from at least one of a monohydric alcohol (e.g., methanol, ethanol), a dihydric alcohol (e.g., ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol) and a trihydric alcohol (e.g., glycerol). By adopting the above-mentioned embodiment, a porous catalyst with a specific structural distribution can be formed, and the prepared catalyst has better selectivity for 1,2-propylene glycol when used in the preparation of 1,2-propylene glycol from polyhydroxy compounds.

[0040] According to the present invention, in some more preferred embodiments, the alcohol compound is a triol. By adopting the above-mentioned embodiment, a porous catalyst with a specific structural distribution can be formed, and the prepared catalyst has better 1,2-propylene glycol selectivity when used in preparing 1,2-propylene glycol from polyhydroxy compounds.

[0041] According to the present invention, in some embodiments, the mass ratio of the organic acid to the alcohol compound is 0.5-2:1, for example, 0.5:1, 1:1, 1.5:1, 2:1, or a range consisting of any two of the above ratios. By adopting the above embodiment, a porous catalyst with a specific structural distribution can be formed, and the prepared catalyst has better 1,2-propylene glycol selectivity when used in the preparation of 1,2-propylene glycol from polyhydroxy compounds.

[0042] According to the present invention, as long as the purpose of the present invention can be achieved, the type of the foaming agent is not particularly limited. In some embodiments, the foaming agent is selected from azo compounds, preferably at least one of diisopropyl azodicarboxylate, diethyl azodicarboxylate and azoaminobenzene.

[0043] According to the present invention, as long as the purpose of the present invention can be achieved, the type of the Ce source is not particularly limited. In some embodiments, the Ce source includes at least one of cerium nitrate hexahydrate, cerium acetate, cerium chloride heptahydrate and cerium sulfate.

[0044] According to the present invention, as long as the purpose of the present invention can be achieved, the type of the Ni source is not particularly limited. In some embodiments, the Ni source includes at least one of nickel nitrate hexahydrate, nickel acetate, nickel chloride and nickel sulfate. In the embodiments of the present invention, nickel nitrate hexahydrate is used as the Ni source for illustration, but the present invention is not limited thereto.

[0045] According to the present invention, in some embodiments, the solvent includes water. By adopting the above-mentioned embodiment, a porous catalyst with a specific structural distribution can be formed, and the prepared catalyst has better 1,2-propylene glycol selectivity when used in preparing 1,2-propylene glycol from polyhydroxy compounds.

[0046] According to the present invention, in some embodiments, the mass ratio of the template to the foaming agent is 0.1-10:1, for example, 0.1:1, 1:1, 2:1, 3:1, 4:1, 5:1, 7:1, 8:1, 10:1, or a range consisting of any two of the above values. The porous catalyst prepared by the above embodiment has better selectivity for 1,2-propylene glycol when used in the preparation of 1,2-propylene glycol from polyhydroxy compounds.

[0047] According to the present invention, in some preferred embodiments, the mass ratio of the template to the foaming agent is 1-5: 1. The porous catalyst prepared by the above embodiment has better 1,2-propylene glycol selectivity when used for preparing 1,2-propylene glycol from polyhydroxy compounds.

[0048] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of Ni source and Ce source is not particularly limited, and those skilled in the art can select the content of Ni source and Ce source according to the actual content of Ce element and Ni element required in the catalyst. In some embodiments, the Ni source is calculated as Ni element, the Ce source is calculated as Ce element, and the mass ratio of the Ni source to the Ce source is above 0.05. The porous catalyst prepared by the above embodiment has better selectivity for 1,2-propylene glycol when used for preparing 1,2-propylene glycol from polyhydroxy compounds.

[0049] According to the present invention, in some preferred embodiments, the mass ratio of the Ni source to the Ce source is 0.05-0.6: 1, preferably 0.2-0.5: 1. The porous catalyst prepared by the above embodiment has better 1,2-propylene glycol selectivity when used for preparing 1,2-propylene glycol from polyhydroxy compounds.

[0050] The porous catalyst prepared by the above-mentioned embodiment has better selectivity for 1,2-propylene glycol when used for preparing 1,2-propylene glycol from polyhydroxy compounds.

[0051] According to the present invention, in some embodiments, the mass ratio of the template to the Ce source is 0.1-1:1, for example, 0.1:1, 0.3:1, 0.5:1, 0.7:1, 1:1, or a range consisting of any two of the above ratios. The porous catalyst prepared by the above embodiment has better selectivity for 1,2-propylene glycol when used in the preparation of 1,2-propylene glycol from polyhydroxy compounds.

[0052] According to the present invention, in some preferred embodiments, the mass ratio of the template to the Ce source is 0.5-1: 1. The porous catalyst prepared by the above embodiment has better 1,2-propylene glycol selectivity when used for preparing 1,2-propylene glycol from polyhydroxy compounds.

[0053] According to the present invention, when preparing the porous catalyst, the amount of solvent used is not particularly limited, as long as the raw materials in the system can be better contacted and reacted. Preferably, the total mass percentage of Ce source, Ni source, template and foaming agent in the solvent is 30-90%, preferably 50-80%.

[0054] According to the present invention, in some embodiments, in step (1), the contact conditions include: the contact temperature is 70-120° C. The aforementioned embodiment is used to facilitate the initial action of the foaming agent in the system to form a porous catalyst with better performance.

[0055] According to the present invention, it should be noted that, during the contacting in step (1), the Ce source, Ni source, template, foaming agent and solvent may be mixed and stirred evenly, and the contacting time is not particularly limited as long as the contacting forms a gel.

[0056] In the present invention, if the temperature is not mentioned during mixing and stirring, it means that the mixing and stirring are carried out at room temperature.

[0057] According to the present invention, in step (1), optional drying means that drying can be performed or not performed as required, preferably drying is performed. In some embodiments, the drying conditions include: drying at 30-100° C. for 0.25-44 hours, preferably drying at 35-90° C. for 0.5-36 hours, and more preferably drying at 50-85° C. for 6-24 hours under an inert gas or air atmosphere.

[0058] According to the present invention, in some embodiments, in step (1), the conditions for the first calcination include: a calcination temperature of 300-800° C., preferably 400-600° C. The above embodiment is adopted to facilitate the template agent and the foaming agent to work together in the system to form a porous catalyst with a specific structural distribution, and when the catalyst is used to prepare 1,2-propylene glycol from polyhydroxy compounds, it has better 1,2-propylene glycol selectivity.

[0059] According to the present invention, in some embodiments, in step (1), the conditions for the first calcination include: the reaction time is 1-24 hours, preferably 2-10 hours.

[0060] According to the present invention, in some embodiments, in step (2), the conditions for the second calcination include: a calcination temperature of 300-800° C. The above embodiment can form a specific porous catalyst, and when the catalyst is used to prepare 1,2-propylene glycol from polyhydroxy compounds, it has better 1,2-propylene glycol selectivity.

[0061] According to the present invention, in some embodiments, in step (2), the conditions for the second calcination include: the calcination time is 0.5-12h.

[0062] In the present invention, the reducing atmosphere refers to other gases having a reducing effect, preferably hydrogen.

[0063] The third aspect of the present invention provides the use of the catalyst of the present invention in hydrolysis and hydrogenation reactions.

[0064] When the catalyst of the present invention is used in hydrolysis and hydrogenation reactions, the substrate conversion rate is very high. During the reaction process, the metal active sites can be effectively stabilized, thereby increasing the cyclic stability of the catalyst.

[0065] According to the application of the catalyst of the present invention, in some embodiments, the catalyst is used for hydrolysis and hydrogenation of polyhydroxy compounds to prepare 1,2-propylene glycol.

[0066] In the present invention, the catalyst of the present invention is used for the hydrolysis and hydrogenation of polyhydroxy compounds to prepare 1,2-propylene glycol, and the substrate conversion rate and the product 1,2-propylene glycol selectivity are very high. During the reaction process, the metal active sites can be effectively stabilized, thereby increasing the cyclic stability of the catalyst.

[0067] A fourth aspect of the present invention provides a method for preparing 1,2-propylene glycol, the method comprising: hydrolyzing and hydrogenating a polyhydroxy compound in the presence of water, hydrogen and the catalyst of the present invention.

[0068] According to the present invention, in some embodiments, the polyhydroxy compound is selected from at least one of starch, cellulose, sucrose, glucose and fructose.

[0069] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of the catalyst is not particularly limited. Based on the conversion rate of the catalyst reaction substrate and economic considerations, in some embodiments, the mass ratio of the polyhydroxy compound to the catalyst is 0.2-10:1, preferably 0.5-4:1.

[0070] According to the present invention, in some embodiments, the mass ratio of water to polyhydroxy compound is 4-1000:1, preferably 10-100:1.

[0071] According to the present invention, in some embodiments, the filling hydrogen pressure is 0.5-10 MPa, preferably 1-6 MPa.

[0072] According to the present invention, in some embodiments, the hydrolysis and hydrogenation conditions include: the reaction temperature is 150-300°C, preferably 200-245°C.

[0073] According to the present invention, in some embodiments, the hydrolysis and hydrogenation conditions include: the reaction time is 0.5-48h, preferably 0.5-4h.

[0074] The present invention will be described in detail below by way of examples. In the following examples and comparative examples:

[0075] The method for preparing 1,2-propylene glycol is as follows: the reaction is carried out in a closed reactor. 0.1 g of catalyst, 0.25 g of glucose and 25 mL of deionized water are added to a high-pressure reactor with stirring, hydrogen is introduced for replacement three times, and then hydrogen is filled to 4 MPa and sealed; the temperature is raised to 240° C. by a program heating jacket, and magnetic stirring is used and then stirred; the reaction is carried out at 245° C. for 2 hours, and the product in the reaction liquid is quantitatively analyzed by gas chromatography, and the raw material in the reaction liquid is quantitatively analyzed by liquid chromatography.

[0076] The reaction product 1,2-propylene glycol was qualitatively analyzed by gas chromatography-mass spectrometry (GC-MS), and the yield of the product 1,2-propylene glycol and the conversion rate of the reaction substrate glucose were analyzed by gas chromatography (GC). The gas chromatography-mass spectrometer was Agilent 7890A of Agilent Corporation of the United States, the chromatographic column was HP-5 non-polar capillary column (30m, 0.53mm), the gas chromatograph was Agilent 7890B, the detector was hydrogen flame ionization detector (FID), and the chromatographic column was SE-54 capillary column (30m, 0.53mm).

[0077] The conversion rate of glucose, the yield of 1,2-propylene glycol and the selectivity of 1,2-propylene glycol were calculated according to the following formula:

[0078] Glucose conversion rate % = (molar amount of glucose participating in the reaction) / (molar amount of glucose as the initial reaction substrate) × 100%;

[0079] Yield of product 1,2-propylene glycol (%) = (the number of carbon atoms corresponding to the molar amount of 1,2-propylene glycol generated by the reaction) / (the number of carbon atoms corresponding to the molar amount of glucose, the initial reaction substrate) × 100%;

[0080] The selectivity of the product 1,2-propylene glycol (%) = (the number of carbon atoms corresponding to the molar amount of 1,2-propylene glycol generated by the reaction) / (the number of carbon atoms corresponding to the molar amount of the initial reaction substrate glucose) × 100%.

[0081] Example 1

[0082] Preparation of porous catalysts:

[0083] (1) 20 g of cerium nitrate hexahydrate, 3.92 g of nickel nitrate hexahydrate, 5 g of citric acid, 5 g of glycerol, 50 g of water, and 5 g of diisopropyl azodicarboxylate were mixed and stirred uniformly, then placed in an 80° C. water bath and heated and stirred until a gel was formed, then placed in an 85° C. oven and heated for 24 h, and finally calcined in a muffle furnace at 600° C. for 4 h to obtain an aerogel sample;

[0084] (2) The aerogel sample obtained in step (1) was heated to 450° C. in a hydrogen atmosphere and calcined for 2 h to obtain a porous catalyst.

[0085] The SEM images of the catalyst are shown in Figure 1 As shown, the obtained catalyst has a macroporous and mesoporous structure, the macropore diameter range is 60-30000nm; the mesopore diameter range is 2-50nm;

[0086] The catalyst has a microporous structure and the specific surface area of ​​the catalyst ranges from 50 to 150 m 2 / g;

[0087] The X-ray photoelectron spectroscopy (XPS) of the Ce element contained in the catalyst is as follows: Figure 2 As shown, it shows that Ce mainly exists in the form of +4 valence; the X-ray photoelectron spectrum (XPS) of Ni element contained in the catalyst is shown in Figure 3 As shown, it means that Ni mainly exists in the form of 0 valence;

[0088] The XRD spectrum of the catalyst is shown in Figure 4 As shown, in the XRD spectrum of the obtained catalyst, diffraction peaks belonging to CeO2 appear at 2θ of 28.5±0.5, 33±0.5, 47.4±0.5, 56.3±0.5, 59±0.5 and 69.3±0.5, and diffraction peaks belonging to Ni appear at θ of 44.5±0.5 and 51.8±0.5; there are no diffraction peaks at 20±0.5, 40±0.5 and 50±0.5.

[0089] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0090] Example 2

[0091] The method of Example 1 is followed, except that in step (1), 20 g of cerium nitrate hexahydrate is replaced by 11.8 g of cerium acetate; the rest is the same as in Example 1, and a porous catalyst is finally obtained.

[0092] SEM images of the catalyst and Figure 1 Similarly, the obtained catalyst has a macroporous and mesoporous structure, with the macropore size ranging from 60 to 30000 nm and the mesopore size ranging from 2 to 50 nm.

[0093] The catalyst has a microporous structure and the specific surface area of ​​the catalyst ranges from 50 to 150 m 2 / g;

[0094] X-ray photoelectron spectroscopy (XPS) of Ce element contained in the catalyst and Figure 2 Similar to the figure, it shows that Ce mainly exists in the form of +4 valence; the X-ray photoelectron spectroscopy (XPS) of the Ni element contained in the catalyst is similar to Figure 3Similarly, it means that Ni mainly exists at 0 valence;

[0095] The XRD spectra of the catalysts Figure 4 Similarly, diffraction peaks attributed to CeO2 appear at 2θ of 28.5±0.5, 33±0.5, 47.4±0.5, 56.3±0.5, 59±0.5 and 69.3±0.5, and diffraction peaks attributed to Ni appear at θ of 44.5±0.5 and 51.8±0.5; there are no diffraction peaks at 20±0.5, 40±0.5 and 50±0.5.

[0096] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0097] Example 3

[0098] The method of Example 1 is followed, except that in step (1), 20 g of cerium nitrate hexahydrate is replaced by 17.2 g of cerium chloride heptahydrate; the rest is the same as Example 1, and a porous catalyst is finally obtained.

[0099] The SEM images of the catalyst are shown in Figure 1 As shown, the obtained catalyst has a macroporous and mesoporous structure, the macropore diameter range is 60-30000nm; the mesopore diameter range is 2-50nm;

[0100] The catalyst has a microporous structure and the specific surface area of ​​the catalyst ranges from 50 to 150 m 2 / g;

[0101] XPS spectra of the catalyst and Figure 2 , 3 is similar, indicating that Ce element mainly exists in the form of +4 valence, and Ni mainly exists in the form of 0 valence;

[0102] The XRD spectra of the catalysts Figure 4 Similarly; diffraction peaks belonging to CeO2 appear at 2θ of 28.5±0.5, 33±0.5, 47.4±0.5, 56.3±0.5, 59±0.5 and 69.3±0.5, and diffraction peaks belonging to Ni appear at θ of 44.5±0.5 and 51.8±0.5; there are no diffraction peaks at 20±0.5, 40±0.5 and 50±0.5.

[0103] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0104] Example 4

[0105] The method of Example 1 is followed, except that in step (1), glycerol is replaced by ethylene glycol; the rest is the same as Example 1, and a porous catalyst is finally obtained.

[0106] The SEM images of the catalyst are shown in Figure 1 As shown, the obtained catalyst has a macroporous and mesoporous structure, the macropore diameter range is 60-30000nm; the mesopore diameter range is 2-50nm;

[0107] The catalyst has a microporous structure and the specific surface area of ​​the catalyst ranges from 50 to 150 m 2 / g;

[0108] X-ray photoelectron spectroscopy (XPS) of Ce element contained in the catalyst and Figure 2 Similar to the figure, it shows that Ce mainly exists in the form of +4 valence; the X-ray photoelectron spectroscopy (XPS) of the Ni element contained in the catalyst is similar to Figure 3 Similarly, this indicates that Ni mainly exists at 0 valence.

[0109] The XRD spectra of the catalysts Figure 4 Similarly, it shows that Ce mainly exists in the form of +4 valence; the X-ray photoelectron spectroscopy (XPS) of the Ni element contained in the catalyst is shown in Figure 3 As shown, it is shown that Ni mainly exists in the form of 0 valence.

[0110] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0111] Example 5

[0112] The method of Example 1 is followed, except that in step (1), citric acid is replaced by oxalic acid; the rest is the same as Example 1, and a porous catalyst is finally obtained.

[0113] SEM images of the catalyst and Figure 1 Similarly, the obtained catalyst has a macroporous and mesoporous structure, with the macropore size ranging from 60 to 30000 nm and the mesopore size ranging from 2 to 50 nm.

[0114] The catalyst has a microporous structure and the specific surface area of ​​the catalyst ranges from 50 to 150 m 2 / g;

[0115] X-ray photoelectron spectroscopy (XPS) of Ce element contained in the catalyst and Figure 2 Similar to the figure, it shows that Ce mainly exists in the form of +4 valence; the X-ray photoelectron spectroscopy (XPS) of the Ni element contained in the catalyst is similar to Figure 3 Similarly, it means that Ni mainly exists at 0 valence;

[0116] The XRD spectra of the catalysts Figure 4 Similarly, diffraction peaks attributed to CeO2 appear at 2θ of 28.5±0.5, 33±0.5, 47.4±0.5, 56.3±0.5, 59±0.5 and 69.3±0.5, and diffraction peaks attributed to Ni appear at θ of 44.5±0.5 and 51.8±0.5; there are no diffraction peaks at 20±0.5, 40±0.5 and 50±0.5;

[0117] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0118] Example 6

[0119] The method of Example 1 is followed, except that in step (1), diisopropyl azodicarboxylate is replaced by diethyl azodicarboxylate; the rest is the same as in Example 1, and a porous catalyst is finally obtained.

[0120] SEM images of the catalyst and Figure 1 Similarly, the obtained catalyst has a macroporous and mesoporous structure, with the macropore size ranging from 60 to 30000 nm and the mesopore size ranging from 2 to 50 nm.

[0121] The catalyst has a microporous structure and the specific surface area of ​​the catalyst ranges from 50 to 150 m 2 / g;

[0122] X-ray photoelectron spectroscopy (XPS) of Ce element contained in the catalyst and Figure 2 Similar to the figure, it shows that Ce mainly exists in the form of +4 valence; the X-ray photoelectron spectroscopy (XPS) of the Ni element contained in the catalyst is similar to Figure 3 Similarly, it means that Ni mainly exists at 0 valence;

[0123] The XRD spectra of the catalysts Figure 4 Similarly, diffraction peaks attributed to CeO2 appear at 2θ of 28.5±0.5, 33±0.5, 47.4±0.5, 56.3±0.5, 59±0.5 and 69.3±0.5, and diffraction peaks attributed to Ni appear at θ of 44.5±0.5 and 51.8±0.5; there are no diffraction peaks at 20±0.5, 40±0.5 and 50±0.5;

[0124] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0125] Example 7

[0126] The method of Example 1 is followed, except that in step (1), the amount of nickel nitrate hexahydrate is replaced by 7.84 g; the rest is the same as Example 1, and a porous catalyst is finally obtained.

[0127] SEM images of the catalyst and Figure 1 Similarly, the obtained catalyst has a macroporous and mesoporous structure, with the macropore size ranging from 60 to 30000 nm and the mesopore size ranging from 2 to 50 nm.

[0128] The catalyst has a microporous structure and the specific surface area of ​​the catalyst ranges from 50 to 150 m 2 / g;

[0129] X-ray photoelectron spectroscopy (XPS) of Ce element contained in the catalyst and Figure 2 Similar to the figure, it shows that Ce mainly exists in the form of +4 valence; the X-ray photoelectron spectroscopy (XPS) of the Ni element contained in the catalyst is similar to Figure 3 Similarly, it means that Ni mainly exists at 0 valence;

[0130] The XRD spectra of the catalysts Figure 4 Similarly, diffraction peaks attributed to CeO2 appear at 2θ of 28.5±0.5, 33±0.5, 47.4±0.5, 56.3±0.5, 59±0.5 and 69.3±0.5, and diffraction peaks attributed to Ni appear at θ of 44.5±0.5 and 51.8±0.5; there are no diffraction peaks at 20±0.5, 40±0.5 and 50±0.5.

[0131] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0132] Example 8

[0133] The method of Example 1 is followed, except that in step (1), the amount of nickel nitrate hexahydrate is replaced by 1.96 g; the rest is the same as Example 1, and a porous catalyst is finally obtained.

[0134] SEM images of the catalyst and Figure 1 Similarly, the obtained catalyst has a macroporous and mesoporous structure, with the macropore size ranging from 60 to 30000 nm and the mesopore size ranging from 2 to 50 nm.

[0135] The catalyst has a microporous structure and the specific surface area of ​​the catalyst ranges from 50 to 150 m 2 / g;

[0136] X-ray photoelectron spectroscopy (XPS) of Ce element contained in the catalyst and Figure 2 Similar to the figure, it shows that Ce mainly exists in the form of +4 valence; the X-ray photoelectron spectroscopy (XPS) of the Ni element contained in the catalyst is similar to Figure 3 Similarly, it means that Ni mainly exists at 0 valence;

[0137] The XRD spectra of the catalysts Figure 4 Similarly, diffraction peaks attributed to CeO2 appear at 2θ of 28.5±0.5, 33±0.5, 47.4±0.5, 56.3±0.5, 59±0.5 and 69.3±0.5, and diffraction peaks attributed to Ni appear at θ of 44.5±0.5 and 51.8±0.5; there are no diffraction peaks at 20±0.5, 40±0.5 and 50±0.5.

[0138] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0139] Example 9

[0140] The method of Example 1 is followed, except that dinitrosopentamethylenetetramine is used to replace diisopropyl azodicarboxylate; the rest is the same as Example 1, and a porous catalyst is finally obtained.

[0141] SEM images of the catalyst and Figure 1 Similarly, the obtained catalyst has a macroporous and mesoporous structure, with the macropore size ranging from 60 to 30000 nm and the mesopore size ranging from 2 to 50 nm.

[0142] The catalyst has a microporous structure and the specific surface area of ​​the catalyst ranges from 0 to 50 m 2 / g;

[0143] X-ray photoelectron spectroscopy (XPS) of Ce element contained in the catalyst and Figure 2 Similar to the figure, it shows that Ce mainly exists in the form of +4 valence; the X-ray photoelectron spectroscopy (XPS) of the Ni element contained in the catalyst is similar to Figure 3 Similarly, it means that Ni mainly exists at 0 valence;

[0144] The XRD spectra of the catalysts Figure 4 Similarly, diffraction peaks attributed to CeO2 appear at 2θ of 28.5±0.5, 33±0.5, 47.4±0.5, 56.3±0.5, 59±0.5 and 69.3±0.5, and diffraction peaks attributed to Ni appear at θ of 44.5±0.5 and 51.8±0.5; there are no diffraction peaks at 20±0.5, 40±0.5 and 50±0.5.

[0145] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0146] Example 10

[0147] The method of Example 1 was followed, except that the amount of citric acid was 3 g, the amount of glycerol was 3 g, and the amount of diisopropyl azodicarboxylate was 9 g; the rest was the same as Example 1, and a porous catalyst was finally obtained.

[0148] SEM images of the catalyst and Figure 1 Similarly, the obtained catalyst has a macroporous and mesoporous structure, with the macropore size ranging from 60 to 30000 nm and the mesopore size ranging from 2 to 50 nm.

[0149] The catalyst has a microporous structure and the specific surface area of ​​the catalyst ranges from 0 to 50 m 2 / g;

[0150] X-ray photoelectron spectroscopy (XPS) of Ce element contained in the catalyst and Figure 2 Similar to the figure, it shows that Ce mainly exists in the form of +4 valence; the X-ray photoelectron spectroscopy (XPS) of the Ni element contained in the catalyst is similar to Figure 3 Similarly, it means that Ni mainly exists at 0 valence;

[0151] The XRD spectra of the catalysts Figure 4 Similarly, diffraction peaks attributed to CeO2 appear at 2θ of 28.5±0.5, 33±0.5, 47.4±0.5, 56.3±0.5, 59±0.5 and 69.3±0.5, and diffraction peaks attributed to Ni appear at θ of 44.5±0.5 and 51.8±0.5; there are no diffraction peaks at 20±0.5, 40±0.5 and 50±0.5.

[0152] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0153] Embodiment 11

[0154] The method of Example 1 was followed, except that citric acid was 6.5 g, glycerol was 6.5 g, and diisopropyl azodicarboxylate was 2 g; the rest was the same as Example 1, and a porous catalyst was finally obtained.

[0155] SEM images of the catalyst and Figure 1 Similarly, the obtained catalyst has a macroporous and mesoporous structure, with the macropore size ranging from 60 to 30000 nm and the mesopore size ranging from 2 to 50 nm.

[0156] The catalyst has a microporous structure and the specific surface area of ​​the catalyst ranges from 0 to 100 m 2 / g;

[0157] X-ray photoelectron spectroscopy (XPS) of Ce element contained in the catalyst and Figure 2 Similar to the figure, it shows that Ce mainly exists in the form of +4 valence; the X-ray photoelectron spectroscopy (XPS) of the Ni element contained in the catalyst is similar to Figure 3 Similarly, it means that Ni mainly exists at 0 valence;

[0158] The XRD spectra of the catalysts Figure 4 Similarly, diffraction peaks attributed to CeO2 appear at 2θ of 28.5±0.5, 33±0.5, 47.4±0.5, 56.3±0.5, 59±0.5 and 69.3±0.5, and diffraction peaks attributed to Ni appear at θ of 44.5±0.5 and 51.8±0.5; there are no diffraction peaks at 20±0.5, 40±0.5 and 50±0.5.

[0159] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0160] Comparative Example 1

[0161] Preparation of catalyst:

[0162] (1) 20 g of cerium nitrate hexahydrate, 3.92 g of nickel nitrate hexahydrate, and 50 g of water were mixed and stirred evenly, then placed in an oven at 85° C. for 24 h, and finally calcined in a muffle furnace at 600° C. for 4 h to obtain a sample;

[0163] (2) The obtained sample was heated to 450°C in a hydrogen atmosphere and calcined for 2 h to obtain a catalyst.

[0164] The obtained catalyst has a non-porous structure;

[0165] The Ce element in the catalyst mainly exists in the form of +4 valence, and Ni mainly exists in the form of 0 valence.

[0166] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0167] Comparative Example 2

[0168] Preparation of porous catalysts:

[0169] 20 g of cerium nitrate hexahydrate, 3.92 g of nickel nitrate hexahydrate, 5 g of citric acid, 5 g of glycerol, 50 g of water, and 5 g of diisopropyl azodicarboxylate were mixed and stirred evenly, placed in an 80°C water bath and heated with stirring until a gel was formed, then placed in an 85°C oven and heated for 24 hours, and finally calcined in a muffle furnace at 600°C for 4 hours to obtain a porous catalyst.

[0170] The Ce element in the catalyst mainly exists in the form of +4 valence, and Ni mainly exists in the form of +2 valence.

[0171] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0172] Comparative Example 3

[0173] The method of Example 1 is followed, except that in step (1), nickel nitrate hexahydrate is replaced by cobalt nitrate hexahydrate; the rest is the same as Example 1, and a porous catalyst is finally obtained.

[0174] The catalyst has a macroporous and mesoporous structure, with the macropore diameter ranging from 60 to 30000 nm and the mesopore diameter ranging from 2 to 50 nm.

[0175] The catalyst has a microporous structure and the specific surface area of ​​the catalyst ranges from 50 to 150 m 2 / g;

[0176] The Ce element in the catalyst mainly exists in the form of +4 valence, and Co mainly exists in the form of 0 valence.

[0177] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0178] Comparative Example 4

[0179] The method of Example 1 is followed, except that in step (1), 3.92 g of nickel nitrate hexahydrate is replaced by 5.6 g of ferric nitrate nonahydrate; the rest is the same as Example 1, and a porous catalyst is finally obtained.

[0180] The catalyst has a macroporous and mesoporous structure, with the macropore diameter ranging from 60 to 30000 nm and the mesopore diameter ranging from 2 to 50 nm.

[0181] The catalyst has a microporous structure and a specific surface area of ​​50-150m 2 / g;

[0182] The Ce element in the catalyst mainly exists in the form of +4 valence, and Fe mainly exists in the form of 0 valence.

[0183] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0184] Comparative Example 5

[0185] The method of Example 1 is followed, except that in step (1), 3.92 g of nickel nitrate hexahydrate is replaced by 3.7 g of copper nitrate monohydrate; the rest is the same as in Example 1, and the catalyst is finally obtained.

[0186] The catalyst has a macroporous and mesoporous structure, with the macropore diameter ranging from 60 to 30000 nm and the mesopore diameter ranging from 2 to 50 nm.

[0187] The catalyst has a microporous structure and a specific surface area of ​​50-150m 2 / g;

[0188] The Ce element in the catalyst mainly exists in the form of +4 valence, and Cu mainly exists in the form of 0 valence;

[0189] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0190] Comparative Example 6

[0191] The method of Example 1 is followed, except that no foaming agent is used; the rest is the same as Example 1, and a porous catalyst is finally obtained.

[0192] The catalyst has a macroporous and mesoporous structure, with the macropore diameter ranging from 50-200nm and the mesopore diameter ranging from 2-50nm.

[0193] The catalyst does not have a microporous structure and the specific surface area of ​​the catalyst is 0m 2 / g;

[0194] X-ray photoelectron spectroscopy (XPS) of Ce element contained in the catalyst and Figure 2 Similar to the figure, it shows that Ce mainly exists in the form of +4 valence; the X-ray photoelectron spectroscopy (XPS) of the Ni element contained in the catalyst is similar to Figure 3 Similarly, it means that Ni mainly exists at 0 valence;

[0195] The XRD spectra of the catalysts Figure 4Similarly, diffraction peaks attributed to CeO2 appear at 2θ of 28.5±0.5, 33±0.5, 47.4±0.5, 56.3±0.5, 59±0.5 and 69.3±0.5, and diffraction peaks attributed to Ni appear at θ of 44.5±0.5 and 51.8±0.5; there are no diffraction peaks at 20±0.5, 40±0.5 and 50±0.5;

[0196] The catalyst composition, as well as the results of glucose conversion rate, 1,2-propylene glycol yield, and 1,2-propylene glycol selectivity in the preparation of 1,2-propylene glycol using the catalyst are shown in Table 1.

[0197] Table 1

[0198]

[0199] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A porous catalyst, characterized in that The catalyst comprises Ce oxide and Ni distributed on the Ce oxide; wherein in the XRD spectrum of the catalyst, diffraction peaks exist at 44.5±0.5 and / or 51.8±0.5; and the catalyst has a microporous structure.

2. The catalyst according to claim 1, wherein In the XRD spectrum of the catalyst, at least one diffraction peak exists at 2θ of 28.5±0.5, 33±0.5, 44.5±0.5, 47.4±0.5, 51.8±0.5, 56.3±0.5, 59±0.5 and 69.3±0.5; Preferably, in the XRD spectrum of the catalyst, there are no diffraction peaks at 20±0.5, 40±0.5 and 50±0.

5.

3. The catalyst according to claim 1 or 2, wherein The catalyst has a macroporous structure and a mesoporous structure, preferably the macroporous pore size of the catalyst is in the range of 60-30000 nm, and / or the mesoporous pore size of the catalyst is in the range of 2-50 nm; and / or The specific surface area of ​​the catalyst is in the range of 50-150 m 2 / g.

4. The catalyst according to any one of claims 1 to 3, wherein In the catalyst, the mass ratio of Ni element to Ce element is not less than 0.064, preferably 0.064-0.53:

1.

5. A method for preparing the porous catalyst according to any one of claims 1 to 4, characterized in that: The preparation method comprises: (1) contacting a Ce source, a Ni source, a template, a foaming agent and a solvent to form a gel, optionally drying, and then performing a first calcination to obtain an aerogel; (2) The aerogel is subjected to a second calcination in a reducing atmosphere.

6. The preparation method according to claim 5, wherein: The template agent includes organic acid and alcohol compound; Preferably, the organic acid is selected from polybasic acids, preferably at least one selected from dibasic acids, tribasic acids and tetrabasic acids, more preferably tribasic acids; and / or The alcohol compound is selected from at least one of monohydric alcohol, dihydric alcohol and trihydric alcohol, preferably trihydric alcohol; and / or The mass ratio of the organic acid to the alcohol compound is 0.5-2:

1.

7. The preparation method according to claim 5 or 6, wherein: The foaming agent is selected from azo compounds, preferably at least one of diisopropyl azodicarboxylate, diethyl azodicarboxylate and azoaminobenzene; and / or The solvent comprises water; and / or The mass ratio of the template agent to the foaming agent is 0.1-10:1, preferably 1-5:1; and / or The Ni source is calculated as Ni element, and the Ce source is calculated as Ce element, and the mass ratio of the Ni source to the Ce source is above 0.05, preferably 0.05-0.6:1, and preferably 0.2-0.5:1; and / or The mass ratio of the template to the Ce source is 0.1-1:1, preferably 0.5-1:

1.

8. The preparation method according to any one of claims 5 to 7, wherein: In step (1), the contact conditions include: a contact temperature of 70-120° C.; and / or In step (1), the conditions for the first calcination include: a calcination temperature of 300-800°C, preferably 400-600°C; and / or a reaction time of 1-24h, preferably 2-10h; and / or In step (2), the conditions for the second calcination include: a calcination temperature of 300-800° C.; and / or a calcination time of 0.5-12 h.

9. Use of the catalyst according to any one of claims 1 to 5 in hydrolysis and hydrogenation reactions, Preferably, the catalyst is used for the hydrolysis and hydrogenation of polyhydroxy compounds to prepare 1,2-propylene glycol.

10. A method for preparing 1,2-propylene glycol, characterized in that: The method includes: In the presence of water, hydrogen and the catalyst according to any one of claims 1 to 4, the polyhydroxy compound is hydrolyzed and hydrogenated; Preferably, the polyol is selected from at least one of starch, cellulose, sucrose, glucose and fructose; and / or The mass ratio of the polyhydroxy compound to the catalyst is 0.2-10:1, preferably 0.5-4:1; and / or The mass ratio of water to polyhydroxy compound is 4-1000:1, preferably 10-100:1; and / or The filling hydrogen pressure is 0.5-10MPa, preferably 1-6MPa; and / or The hydrolysis and hydrogenation conditions include: a reaction temperature of 150-300°C, preferably 200-245°C; and / or a reaction time of 0.5-48h, preferably 0.5-4h.

Citation Information

Patent Citations

  • Method for selectively preparing propylene glycol from sugar-containing compound

    CN102731257A

  • Method for preparing 1, 2-propanediol by adopting jerusalem artichoke as raw material in direct catalytic conversion

    CN103833513A

  • Catalyst for preparation of 1, 2-propylene glycol through glycerol hydrogenation as well as preparation method and application of catalyst

    CN104549347A

  • Method for producing 1,2-propanediol and ethylene glycol from xylose or xylooligosaccharide

    CN106866374A